Ju jitsu - Randall, Pamela (New York : PowerKids Press, 1999)
Introduces the history, basic moves, and terminology of this martial art.
Includes index.
IG 1000
Accelerated Reader AR
Keywords: Jiu-jitsu -- Juvenile literature; Jiu-jitsu.